Fiscal Impact Analysis in TMT Sector - Okore, Nnamdi (Journal of Educational Research and Policies, 2026)
With the evolution of technology and rapid growing of commercial transactions between multinational enterprises, the income derived from the use of intangible property has significantly increased. The world has become a global village and India is also become an integral part of the same. The present globalised business environment permits multinational companies globally to leverage their intellectual property rights in order to create a source of income in countries across the world. Moreover, with an increase in e - commerce, the complexities of cross border transactions have increased. The Telecommunication, Media, and Technology (TMT) business has experienced extraordinary development and transition over for a number of years, and will probably persist in the coming years. The Indian IT sector is divided into four primary sections: information technology (IT), enterprise process management, application development, and equipment.